Professionalism of Christian Religion Education Teachers at Public Elementary Schools in Southeast Minahasa Regency - Meike Rondo; Ellen S. Kambey; Wolter Weol (International Journal of Education, Information Technology, and Others, 2023)
The purpose of this study was to obtain data on the Professionalism of PAK teachers in interpreting and analyzing material, structures, concepts, and scientific mindsets that are relevant to learning Christian Religious Education at Public Elementary Schools in Southeast Minahasa Regency. This study uses a qualitative research approach. The results showed that PAK teachers had not analyzed and interpreted the material, structures, concepts, and scientific mindsets that were relevant to the learning of Christian Religious Education in Public Elementary Schools in Southeast Minahasa Regency because they experienced various obstacles such as not fully understanding the material, structure, concepts, and a scientific mindset that is relevant because the teacher does not read enough. In addition, KKG activities have not been carried out, and there has been no guidance provided by the PAK supervisor. Therefore, efforts that can be made to overcome these problems include teacher initiatives to increase literacy, carry out KKG activities, optimize guidance from PAK supervisors.